Relationship between glycemic control and histochemical myeloperoxidase activity in neutrophils in patients with type 2 diabetes. Issue 1 (December 2015) - Unubol, Mustafa; Yavasoglu, Irfan; Kacar, Firuzan; Guney, Engin; Omurlu, Imran; Ture, Mevlut; Kadikoylu, Gurhan; Bolaman, Zahit
Abstract Background Myeloperoxidase (MPO) is a lysosomal hemoprotein found in the azurophilic granules in neutrophils. Myeloperoxidase plays an important role in oxygen-dependent killing of bacteria, fungi, virus and malignant cells. Diabetes mellitus (DM) is listed among conditions that may lead to secondary MPO deficiency in neutrophils but inconsistent results concerning MPO activity in diabetic patients have been reported in the literature. In this study, we aimed to evaluate the relationship between glycemic control in patients with type 2 DM and MPO activity in neutrophils from a histochemical perspective. Methods The study included 40 patients with type 2 DM with poor glycemic control, 30 patients with type 2 DM with good glycemic control and 31 healthy controls. Peripheral blood smears were analyzed for each patient included in the study. Myeloperoxidase dye was used for staining. Myeloperoxidase ratios in neutrophil were evaluated for proportions of staining with MPO in 100 neutrophils in each smear. SPSS 16.0 version was used for statistical analyses. Results Myeloperoxidase ratios in neutrophils were 70 (58.5–80) in type 2 DM patients with poor glycemic control compared to 80 (73.75–90) in those with good glycemic control and 88 (78–92) in healthy controls. The DM group with poor glycemic control was statistically significantly different from the other groups (p < 0.001). Conclusions Poor glycemic control in diabetic patients results in decreased MPO activity in neutrophils histochemically.